PPARγ and RhoBTB1 in hypertension. Issue 2 (March 2020) - Fang, Shi; Sigmund, Curt D.
Abstract : Purpose of review: This review provides an up-to-date understanding of how peroxisome proliferator activated receptor γ (PPARγ) exerts its cardioprotective effect in the vasculature through its activation of novel PPARγ target genes in endothelium and vascular smooth muscle. Recent findings: In vascular endothelial cells, PPARγ plays a protective role by increasing nitric oxide bioavailability and preventing oxidative stress. RBP7 is a PPARγ target gene enriched in vascular endothelial cells, which is likely to form a positive feedback loop with PPARγ. In vascular smooth muscle cells, PPARγ antagonizes the renin–angiotensin system, maintains vascular integrity, suppresses vasoconstriction, and promotes vasodilation through distinct pathways. Rho-related BTB domain containing protein 1 (RhoBTB1) is a novel PPARγ gene target in vascular smooth muscle cells that mediates the protective effect of PPARγ by serving as a substrate adaptor between the Cullin-3 RING ubiquitin ligase and phosphodiesterase 5, thus restraining its activity through ubiquitination and proteasomal degradation. Summary: In the vasculature, PPARγ exerts its cardioprotective effect through its transcriptional activity in endothelium and vascular smooth muscle. From the understanding of PPARγ's transcription targets in those pathways, novel hypertension therapy target(s) will emerge.